Implementasi Rehabilitasi terhadap Narapidana Narkotika dalam Pembinaan di Lembaga Pemasyarakatan Kelas Iib Lubuk Pakam - Jumaga Sihombing; Mhd. Azhali Siregar; T. Riza Zarzani (Pusat Riset dan Inovasi Nasional, 2025)
The coaching system for drug convicts is carried out in correctional institutions, where Correctional Institutions are a form of criminal punishment (imprisonment). In the rehabilitation process, victims of narcotics abuse are not objects but subjects. Criminal punishment (punishment) is not merely giving suffering to deter, but an element of guidance and coaching with the aim that lawbreakers can realize their mistakes and not repeat their actions again, and can return to society and carry out their social functions properly. The purpose of this study was to find out the concept of fostering convicts through rehabilitation, Implementation of Rehabilitation of Narcotics Prisoners in Lubuk Pakam Class II B Prison, Effectiveness of implementing Narcotics Rehabilitation in Lubuk pakam Class II B. This research is included in the descriptive research with the type of empirical juridical research using qualitative analysis methods.From the results of the research it is known that the concept of rehabilitation in the process of coaching prisoners is aimed not only at the mentality of prisoners but also treating dependence on narcotics themselves so that prisoners can recover physically and mentally. Implementation of rehabilitation is based on the provisions of Law Number 35 of 2009 concerning Narcotics and several rules for the implementation of rehabilitation, the Implementation of Fehabilitation in the Class IIB Lubuk Pakam Penitentiary includes medical rehabilitation and social rehabilitation. The implementation of medical rehabilitation includes the Health Examination Stage, the Detoxification Stage, the mental and emotional stability stage of the sufferer. While social rehabilitation includes personality development and independence development and the application of medical rehabilitation and social rehabilitation at the Lubuk Pakam Class IIB Penitentiary is quite effective in reducing the repetition rate (recidivist) of convicts who have completed their sentence, convicts who have served a period of detention have recovered from dependence on narcotics, but the environment outside the prison can affect the re-use by inmates.